The Evolution of Qur'anic Knowledge Authority from Traditional Transmission to Algorithmic Digital Platforms - Mahfudz, Ahmad; Munib, Abd (Universitas Muhammadiyah Surakarta, 2026)
Changes in media and technology have affected the legitimacy, distribution, and access to Qur'anic knowledge. The formulation of the research problem focuses on how the authority of Qur'anic science has evolved from traditional to rational-legal to technological and its implications for the legitimacy and quality of science. The purpose of this research is to explore the evolution of the scientific authority of the Qur'an, identify challenges and opportunities, and provide recommendations for education and management of digital interpretation. The research method uses a descriptive-analytical qualitative approach based on literature review and documentation studies with the integration of Max Weber's theory of traditional, rational-legal, and charismatic authority as an analytical knife. The results of the study show three findings. First, the traditional authority in classical times was centered on scholars and sanad, guaranteeing the authenticity and authenticity of the text. Second, rational-legal authority through standardized printing mushaf strengthens formal legitimacy and wide distribution. Third, technology authorities in the digital era bring the democratization of access through applications, but face challenges of legitimacy, interpretation accuracy, and algorithm dominance. The significance of the research lies in the systematic understanding of the evolution of the scientific authority of the Qur'an, its implications for education, the regulation of digital interpretation, and the integration of scientific traditions with technological innovation. This research's contribution provides a new conceptual framework for the study of the sociology of religion, Islamic epistemology, and the development of Qur'an applications, while affirming the importance of synergy between traditional authorities and technology to maintain the credibility and sustainability of Qur'anic knowledge.